Learning Using Virtual Shared Workspaces - Moënne, Gerardo; Barnes, Sally; Sutherland, Rosamund (Proceedings of the International Conference on Networked Learning, 2000)
New technologies arc rapidly being introduced into the market and with them come social and political pressure to introduce them into schools. Every new technology is expected to change dramatically the whole learning process therefore their effects tend to be studied in isolation from other tools already in use. Nevertheless, in practice, no single tool has shown itself capable of making a revolutionary change and every new tool is used in conjunction with existing tools. Hence, we believe that every new technology is a gateway to new teaching and learning possibilities and its use is affected by, and affects, the use of tools already in use. Therefore, research should take an holistic look at the whole range of tools, and their use, rather than exploring single tools in isolation. We consider video communication and the ability to share an application to be two of the emerging technologies that, in the near future, will be massively adopted by schools and education programmes. We have reason to believe that providing these new possibilities, for students and teachers, who are already overwhelmed by the set of alternatives, will not be as smooth as with other technologies (Cifuentes, Beller, & Portela, 1999).